Proteomics in pediatric cystic craniopharyngioma - Massimi, Luca (Brain Pathol, 2017)
Adamantinomatous craniopharyngioma (ACP) is still often burdened by a poor prognosis in children as far as the risk of recurrence and the quality of life are concerned. Therefore, many efforts are now dedicated to investigate the molecular characteristics of this tumor aiming at finding new therapeutic options. ACP is prevalently a cystic lesion so that an increasing number of researches are focused on the analysis of its cystic content. In the present article, the main results of the current proteomic analysis (PA) on the ACP fluid are summarized. Both “bottom‐up” and “top‐down” approaches have been utilized. In the bottom‐up approach, proteins and peptides are enzymatically or chemically digested prior to liquid chromatography and mass spectrometry analyses. The bottom‐up approach pointed out several proteins of the inflammation (namely, α2‐HS‐glycoprotein, α1‐antichymotrypsin and apolipoproteins) as possibly involved in the genesis and growth of the cystic component of ACP. The top‐down strategy analyzes proteins and peptides in the intact state, making it particularly suitable for the identification of peptides and low molecular weight proteins and for the characterization of their possible isoforms and post‐translational modifications. The top‐down approach disclosed the presence of the thymosin β family. Thymosin β4, in particular, which is involved in the cytoskeleton organization and migration of several tumors, could play a role in the progression of ACP. Finally, PA was utilized to investigate alterations in cyst fluid character after treatment with interferon‐α. The analyzed samples showed a progressive reduction of the levels of α‐defensins (proteins involved in the inflammatory‐mediated response) after the intracystic injection of interferon‐α, thus reinforcing the hypothesis that inflammation contributes to ACP cyst pathogenesis. Additional studies on the solid component of ACP are still necessary to further validate the previous results and to identify possible markers for targeted therapy.